Synovial Sarcoma of the Hand - Hovsep Ohan; Greg Minassian; Asaad H. Samra; Matthew J. Zdilla (Hindawi Limited, 2020)
The incidence of synovial sarcoma is 1.548 per 1,000,000. Synovial sarcoma localized to the palmar surface should, therefore, be considered extremely rare. This report documents a 34-year-old male with a right hand mass that had been present for a few years, continuing to grow in size. The mass was located at the palm and extended from the mid-third metacarpal to involve all digits except the thumb. The mass was determined to be monophasic synovial sarcoma on histopathologic exam. Fluorescence in situ hybridization for SYT gene rearrangement was positive in 72% of cells. Resection of the mass was followed by radiation and chemotherapy. The patient had a long-term follow-up of 3.5 years with no evidence of any local recurrence of the tumor. This report increases awareness of this extremely rare malignancy-an awareness that is crucial for early diagnosis and improved survival rates. It is more common at younger ages but it can occur at any age, so it should be suspected and included in the differential diagnosis, especially when evaluating slow growing, nonresolving hand lesions.